EMPLOYEE PERFORMANCE: THE ROLE OF TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION (STUDY ON EMPLOYEES OF ONE COMPANY IN THE FOOD AND BAVERAGE FIELD IN BANDUNG) - Nurina Insani; Nenny Rinawati (STMIK Mardira Indonesia, Bandung, 2021)
This study aims to analyze how much influence transformational leadership and work motivation have on employee performance at a company engaged in the food and beverage sector in Bandung. The total population in this study was 75 employees of the company. Data collection techniques are observation, interviews, questionnaires, and literature study. There are two variables in this study, namely, the independent and dependent variables. The independent variable consists of Transformational leadership and employee motivation, and the dependent variable is employee performance. The author conducted this research by testing the validity and reliability of the instrument. Then the data were analyzed using the path analysis method. The results showed that the influence of transformational leadership was partially 31.2%, while for work motivation, it had a partial effect of 32.5%. For all variables of transformational leadership and work motivation on employee performance, it has a simultaneous effect of 63.7%. This research shows a significant effect, and the remaining effect is 36.3% by other factors not examined in this study. Keywords : transformational leadership, work motivation, employee performance.